The effect of other customer perception and need for uniqueness on service experience and revisit intention - Shrestha, Shankar Kumar; Shrestha, Bikash (PYC Nepal Journal of Management, 2021)
Service marketing focuses on service encounter stimuli, such as the servicescape, employee interactions, the core service, and other customers. The studies that have focused on other customers’ role as a social component of the service environment have led to the development of a comprehensive measure of other customer perception. Thus, based on the social impact theory, attraction theory and the theory of uniqueness, the study analysed the effect of Other Customer Perception (OCP), Need for Uniqueness (NFU and their interaction on service experience and revisit intention by employing a scenario-based quasi-experimental research design with a sample of 127 job holder postgraduate management students using convenient sampling technique. The study employed MANOVA GLM model and concludes that while the impact of consumers’ perceptions of other customers’ similarity does influence service experience of the customers, demonstrating that not only the restaurant itself, but also the entities in the surrounding network such as other customers have an impact on service experience and their revisit intention. Therefore, other customer effect, which works as a basis for service experience and revisit intention, should not be neglected when designing the surroundings in restaurant settings.